TOWARD A QUALITY MODEL FOR A UNIVERSITY OF TECHNOLOGY RESEARCH CENTRE IN SOUTH AFRICA - Singh, Penny; Zheng, Jin (South African Journal of Higher Education, 2016)
The New Funding Framework is based on output and weights the components of teaching output and the components of research output for each unit of subsidy invested by the government, higher education funding is thus based on the aggregate research outputs of universities and is driven by specific goals such as to stimulate and reward institutional research (De Villiers and Steyn, 2009; Madue, 2008: 128). Universities of Technology (UoTs) are therefore under pressure to increase their research performance and measurable outputs in particular (Christiansen and Baijnath, 2007; van Zijl, Gericke and Machet, 2006). This has resulted in a corresponding demand for a range of services to support and develop postgraduate students, supervisors and early career researchers. As research in SA UoTs is at an embryonic stage, this study benchmarked SA UoTs with Australian (Aus) UoTs as Australia has a worldwide reputation for academic excellence, offering internationally recognised qualifications with immediate employment and career development opportunities. The aim of this study was to identify best practice in terms of postgraduate research development and support service delivery in the SA and Aus contexts to inform the development of a quality model for postgraduate or research centres (PG/RCs) at UoTs in SA. Using a mixed-methods research approach, this study gathered data from postgraduate students and staff who had experience with PG/RC services. Service quality of the PG/RCs in this study was determined by measuring the service gaps in terms of student perceptions and expectations so that steps may be taken to close these gaps in an attempt to improve service quality. Based on the literature reviewed, best practice gleaned from the findings of this study, and benchmarking with the Aus UoTs; this study proposed a centralized and decentralized PG/RC model for SA UoTs to provide service quality to its ‘customers’.